Case reportSyphilis – issue of the 21st century - Karlińska-Jachowska, Marlena; Chmielnicki, Paweł; Dziankowska-Bartkowiak, Bożena; Waszczykowska, Elżbieta; Torzecka, Jolanta Dorota (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2007)
A substantial increase in syphilis morbidity has been observed for the last few years. It is probably connected with increased migration and hazardous sexual behaviour among young people. We present three cases of secondary recidivans syphilis, characterized by rich manifestation, which were at first misdiagnosed by general practitioners. As atypical primary symptoms within lips were present in the patients, at first herpes simplex infection and squamous cell carcinoma were diagnosed. Diagnostic difficulties and subsequently delay in appropriate treatment resulted in simultaneous development of many symptoms of secondary syphilis. Medical history revealed numerous sexual contacts, including homosexual ones, which was why laboratory examination for HIV infection was performed. In one of the patients anti-HIV antibodies were detected. Described cases are presented because of high didactic value